Short Overview of The Burden of Tuberculosis - Khan MD MS, Ahmad; Fahim, Soma; Muheb MD, Roya; Ahmadi, Shabnam (Clinical Medicine And Health Research Journal, 2024)
Tuberculosis has been a common infectious disease among humans since ancient times. Mycobacterium tuberculosis can affect different parts of the human body – commonly, human lungs. Tuberculosis is one of the significant public health issues in most countries. According the World Health Organization (WHO) globally, tuberculosis kills approximately 2 million people every year, and 10 million new cases were diagnosed in 2019 (WHO, 2020). The primary source of infection in the community is people who have smear-positive Mycobacterium tuberculosis and their sputum. Among people infected with Mycobacterium tuberculosis, 5 to 10% of people might develop clinical manifestations of the disease. The emergence of clinical manifestation is significantly increased in HIV-positive people (Harries & Dye, 2006).